De la métataxe a la médiation linguistique - Franić, Ivana (Linguistica (Ljubljana), 2014)
In his capital work Eléments de syntaxe structurale (1959) Lucien Tesniere introduces the concept of metataxis, structural change occurring during the transition from one language to another. While focusing on structural relationships that are built upon this passage, the author highlights the need to rethink the phrase in the target language. Departing from a purely mechanical perspective, Tesniere paves the way for contrastive analysis, but also for cognitive theories, referring to the concepts of traductions profondes and of the independence of structure and meaning. However, the action-oriented approach presupposes a dynamic process of learning / teaching that places the learner at the center and takes into account all the abilities of this "social actor". In that way the CEFR opens the individual and social dimensions of mediation (Piccardo 2012), which is one of the key concepts of the action-oriented approach. In this paper we outline the conceptual foundations of metataxis and linguistic mediation and then examine the role of translation as the basic operation for the transition from one language to another, specifically in the learner-centred action-oriented approach. We rethink the concept of translation, taking into account its mechanical and structural aspects as well as its individual and social dimensions, which offers many opportunities for language and culture learning. The linguistic structure is considered as an essential component of linguistic mediation.
Keywords: akcijski pristop; didactique des langues; didaktika jezika; mediacija; médiation; metataksa; métataxe; perspective actionnelle; prevajanje; skladnja; strukturalna sintaksa; syntax; syntaxe; syntaxe structurale; Tesniere, Lucien, 1893-1954; traduction; translation; tuji jeziki